The Resilience of the Indigenous People Towards Natural Disasters: Case of Central Mountains of Papua - Normalia Ode Yanthy; Yannice Luma Marnala Sitorus; Anggia Riani Nurmaningtyas (Universitas Andalas, 2022)
The resilience of the indigenous people of Papua towards natural disasters has been questioned because of the large number of casualties post disasters deaths which should have been handled differently considering their knowledge and closeness to nature; thus, it should be easy for them to adapt in times of natural changes. This study is aimed at investigating the resilience of the indigenous people of Papua in the central mountains of Papua towards disasters based on secondary data. Study results showed that the resilience of indigenous people of the central mountains of Papua towards disasters is more influenced by social factors than ecology since, generally, the ecological system in the disaster area in the central mountains of Papua has not experienced much change. The social factors are, among others, the impact of modern civilization, which has not been well adapted by the indigenous people, and the lack of skills of local stakeholders in disaster mitigation. Disaster mitigation should be in the form of improvement of the social condition of indigenous people of the central mountains area of Papua to perfect their civilization towards a more prosperous life